A Comparison of the Spanish and English translation of the Chinese novel "Beijing Coma" - Ku, Menghsun (Estudios de Traducción, 2014)
Beijing Coma is a novel, in which the protagonist Dai Wei tells the Tiananmen events through his memories. After being shot in the Tiananmen Square on June 4, 1989, Dai Wei fell into a coma. Ten years later, he awakes, however, in a paralyzed body, discovering that the world outside has changed and that the citizens’ memories, except of a “vegetable”, have been erased by the government. This study compares the Spanish and English versions of the Chinese novel, with the intention to explore the ideology and translation strategies used by the translators. Since there has been few translation analysis based on the Chinese and Spanish language pairs, this research is expected to provide empirical and pioneering values to observing the objective and mainstream trend in translation.